Pseudomonas aeruginosa enhances anti-PD-1 efficacy in colorectal cancer by activating cytotoxic CD8+ T cells - Chen, Lu; Ruan, Guangcong; Zhao, Xuefei; Yi, Ailin; Xiao, Zhifeng; Tian, Yuting; Cheng, Yi; Chen, Dongfeng; Wei, Yanling (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint therapy for colorectal cancer (CRC) has been found to be unsatisfactory for clinical treatment. Fecal microbiota transplantation (FMT) has been shown to remodel the intestinal flora, which may improve the therapeutic effect of αPD-1. Further exploration of key genera that can sensitize cells to αPD-1 for CRC treatment and preliminary exploration of immunological mechanisms may provide effective guidance for the clinical treatment of CRC.MethodsIn this study, 16S rRNA gene sequencing was analyzed in the fecal flora of both responders and no-responders to αPD-1 treatment, and the therapeutic effect was experimentally verified.ResultsPseudomonas aeruginosa was found to be highly abundant in the fecal flora of treated mice, and Pseudomonas aeruginosa mannose-sensitive hemagglutinin (PA-MSHA) in combination with αPD-1 was effective in the treatment of CRC through the induction of CD8+ T-cell immunological effects.ConclusionThe clinical drug PA-MSHA can be used in combination with αPD-1 for the treatment of CRC as a potential clinical therapeutic option.